(untitled) (Scientific journal of the Fergana State University, 2024)
The article contains information about the state of Usun, which ruled the ancient Central Asian region for several centuries. Information about this country was first mentioned in Chinese sources. The sources contain valuable information about the political, economic and social life of the Usun state, as well as the geography of the state. In addition, the article analyzes some issues in research about the state of Usun